2013
DOI: 10.1177/1756287213498923
|View full text |Cite
|
Sign up to set email alerts
|

Holmium laser enucleation of the prostate: a paradigm shift in benign prostatic hyperplasia surgery

Abstract: Holmium laser enucleation (HoLEP) was developed in the 1990s as a more efficient and cost effective method of benign prostatic hyperplasia surgery than laser vaporization and resection techniques. As a true anatomical enucleation it mimics open prostatectomy and is as durable. There is a significant body of level 1 evidence in support of HoLEP, including 2 metaanalyses and 14 randomized trials which compare HoLEP with a number of other procedures. This review describes the development of and summarizes the evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 56 publications
0
14
0
2
Order By: Relevance
“…Holmium laser therapy has an established role in endoscopic urology, in particular for the treatment of benign prostatic hyperplasia and urolithiasis [ 12 , 13 ]. Although many studies have reported on managing prostatic abscesses with conventional transurethral resection [ 5 , 6 ], using a holmium laser to perform a transurethral approach has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Holmium laser therapy has an established role in endoscopic urology, in particular for the treatment of benign prostatic hyperplasia and urolithiasis [ 12 , 13 ]. Although many studies have reported on managing prostatic abscesses with conventional transurethral resection [ 5 , 6 ], using a holmium laser to perform a transurethral approach has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, there has been a paradigm shift to HoLEP as the primary surgery in modern BPH, which alleviates LUTS and improves urodynamic study (UDS). 6,7) HoLEP with mechanical morcellation can be divided into two processes: gross tissue resection or enucleation and morcellation to extract enucleated prostatic tissue from the body. The early practice of leaving prostate tissue in the bladder after HoLRP caused problems.…”
Section: Introductionmentioning
confidence: 99%
“…Since that time, TURP has been considered the standard surgical treatment of small to moderate-size obstructive BPH. The American Urological Association guidelines define TURP as the ‘‘gold standard’’ surgical treatment for BPH [1-3]. Holmium laser enucleation (HoLEP) was developed in the 1990s as a surgical treatment for BPH that is more effective and safer than laser vaporization and traditional resection techniques.…”
Section: Introductionmentioning
confidence: 99%
“…HoLEP has become the novel standard for the surgical treatment of BPH because it is effective while being less invasive and having a low incidence of complications. The effectiveness and safety of HoLEP to treat BPH are well known; recently, this technique has been used on prostates of various sizes [3]. Many studies have compared the effectiveness of HoLEP and TURP in terms of improvement in voiding symptoms, maximal flow rate (Qmax), postvoid residual volume (PVR), the International Prostate Symptom Score (IPSS), and complications.…”
Section: Introductionmentioning
confidence: 99%